2013
DOI: 10.1159/000346373
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Study of Removal of Protein-Bound Toxins

Abstract: Protein-bound toxins are not efficiently removed by conventional hemodialysis techniques. In order to improve the removal of protein-bound toxins, we performed an in vitro study to evaluate the effects of dilution and pH change on the dissociation of protein-bound toxins from albumin. Human plasma harvested by therapeutic apheresis treatment was diluted with saline or isotonic NaHCO3 solution, and the amounts of the free fractions of indoxyl sulfate (IS) and homocysteine were determined. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…However, it should be noted that these experiments of bilirubin adsorptions on various pure porous carbons are mostly conducted in albumin-free solution, which is contrary to the facts that serum albumin is the most abundant protein in blood and bilirubin exists primarily in the form of albumin-bilirubin complex. [13][14][15] Despite the advantage of high effectiveness for free bilirubin removal, these pure porous carbon adsorbents usually perform poorly on the removal of albumin-bonded bilirubin. For instance, the reported adsorption capacity of carbon nanotube sheets toward bovine serum albumin (BSA)-bonded bilirubin is 9.7 mg g À1 , which is signicantly lower than the values obtained for free bilirubin removal.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that these experiments of bilirubin adsorptions on various pure porous carbons are mostly conducted in albumin-free solution, which is contrary to the facts that serum albumin is the most abundant protein in blood and bilirubin exists primarily in the form of albumin-bilirubin complex. [13][14][15] Despite the advantage of high effectiveness for free bilirubin removal, these pure porous carbon adsorbents usually perform poorly on the removal of albumin-bonded bilirubin. For instance, the reported adsorption capacity of carbon nanotube sheets toward bovine serum albumin (BSA)-bonded bilirubin is 9.7 mg g À1 , which is signicantly lower than the values obtained for free bilirubin removal.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of IS was determined by high performance liquid chromatography. Free fractions (FR) were calculated as below formula ( 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it might be better if IS is dissociated from albumin and excluded during HD therapy. Yamamoto, et al demonstrated in vitro that dilution and pH change of dialysate facilitate IS dissociate from albumin ( 4 ). The predilution mode can dilute the blood before hemodia filter in on-line HDF therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Another area of research concerns altering the dialysis milieu in order to affect the binding of URS to plasma proteins. Examples of this effort which have data supporting their use include using hypertonic solution, the use of albumin-binding site competitors such as tryptophan and docosahexaenoic acid, increasing temperature, plasma dilutions, and pH manipulation of the dialysate [47,[90][91][92][93][94].…”
Section: Dialysismentioning
confidence: 99%